2015
DOI: 10.3892/or.2015.4289
|View full text |Cite
|
Sign up to set email alerts
|

Screening and verification of proteins that interact with HSPC238

Abstract: HSPC238 is a recently identified tumor suppressor and demonstrates ubiquitin ligase E3 enzyme activity. HSPC238 was found to be significantly downregulated in human hepatocellular carcinoma (HCC) in vivo and to inhibit the proliferation and invasion of hepatoma cells in vitro; however, the underlying molecular mechanism is largely unknown. In the present study, we screened for and identified proteins that physically interact with HSPC238. A bait vector for yeast two-hybrid was constructed with human HSPC238 ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…HSPC238 has Ub ligase E3 activity, inhibiting the growth and proliferation of HCC. Mechanistically, HSPC238 functions as a tumor suppressor by promoting the degradation of RPS27a via the UPP (Tan et al, 2015). These studies reported a conclusion similar to that obtained via the GEPIA database: Low RPS27a expression in liver cancer patients is correlated with better overall survival rates (Figure 2).…”
Section: Rps27a In Humansmentioning
confidence: 99%
“…HSPC238 has Ub ligase E3 activity, inhibiting the growth and proliferation of HCC. Mechanistically, HSPC238 functions as a tumor suppressor by promoting the degradation of RPS27a via the UPP (Tan et al, 2015). These studies reported a conclusion similar to that obtained via the GEPIA database: Low RPS27a expression in liver cancer patients is correlated with better overall survival rates (Figure 2).…”
Section: Rps27a In Humansmentioning
confidence: 99%